Large predators and their impact on reindeer husbandry - Åhman, Birgitta; Rasmus, Sirpa; Risvoll, Camilla; Eilertsen, Svein Morten; Norberg, Harri (2022)
Several large predators (wolf, lynx, wolverine, brown bear and eagle) are present within the Fennoscandian reindeer herding area, where reindeer are often their main prey. After being more or less eradicated during the 1800s and early 1900s, predators were gradually protected leading to the recovery of all species. Growing populations of predators evidently lead to increased damage to reindeer and reindeer husbandry. In Fennoscandia, the annual loss of reindeer due to predation is probably around 50,000–100,000 animals. Herders get economic compensation for losses. In Finland and Norway, this is based on the number of predator-killed reindeer that are found, while in Sweden the compensation is based on the number of predators (wolf, lynx or wolverine) or area of the herding district (bear and golden eagle). According to national policy, reindeer husbandry should be taken into account in the management of large predators, but often population goals for the predator override the interests of reindeer husbandry. Although reindeer herders acknowledge that predators have a place in the ecosystem, there is frustration about reimbursement not compensating for actual losses, and that herders’ voices are not heard, and their knowledge not recognized, when it comes to predator management.